(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Cascabela thevetia generally recognized as yellow oleander, Lippold or lucky nut (in English) and Peeli Kaner (in Hindi), is Indigenous to Central America and Mexico and widely distributed in the Indian subcontinent as well, is a medicinally important herb that has long been employed to treat disorders like ulcers, scabies, haemorrhoids, and tumour dissolution. Seven Cardenolides (Compounds 1-7) isolated from fruits of Cascabela thevetia are selected as ligands for in silico pharmacokinetic (ADME properties) and drug-likeness studies via the Swiss ADME online server. Further, molecular docking studies were accomplished for the selected ligands via the Auto Dock Vina module of PyRx to explore the receptor-ligand interaction with β-tubulin (a potential target for anticancer drugs, PDB ID: 1SA0), to find out potential therapeutic ligands for cancer chemotherapy. From the studies performed it was found that most of the ligands (compounds) have the capability of good binding affinity with the receptor, β-tubulin, good drug-likeness and ADME properties among which compounds 3, 6 and 7 are the best drug candidates because they followed the Lipinski rule of 5 with 0 violation and also have good binding affinities (-8.3, -8.0 and -7.9 kcal/mol respectively) against the target protein. Hence, compounds 3, 6 and 7 can be developed as novel therapeutic agents in cancer chemotherapy. Further, a Molecular Dynamics (MD) simulation study of best-docked ligand 3 was performed to establish its stability and validate molecular docking results. Based on simulation results, it may be stated that ligand 3 was firmly attached to the receptor protein during MD simulation since none of the conformations of the receptor-ligand complex were unstable, and no folding or unfolding of the complex took place. Therefore, compound 3 can be considered a good inhibitor of β-tubulin after validation of various parameters of drug discovery.